Friday

July 25, 2014

July 25, 2014

Posted by **Maya** on Sunday, July 14, 2013 at 10:02pm.

f(x) = x2 − 3x, g(x) =√(x+2)

(a) Find (f *g)(x). (Simplify your answer completely.)

(B)Find the domain of f *g. (Enter your answer using interval notation.)

(c) Find (g *f)(x). (Simplify your answer completely.)

(D) Find the domain of g*f. (Enter your answer using interval notation.)

- Algebra 2 help -
**Steve**, Monday, July 15, 2013 at 4:52amf*g = g*f = (x^2-3x)√(x+2)

domain is all reals x >= -2

If you meant ◦ instead of *, then

(f◦g) = f(g) = g^2-3g = (x+2) - 3√(x+2)

(g◦f) = g(f) = √(f+2) = √(x^2-3x)

domain of f◦g is x >= -2

domain of g◦f is x<= 0 or x>= 3

**Related Questions**

algebra 1 help - simplifying square roots 1) find volume of this prism? v=bwh b...

College Algebra - For the given functions f and g, find the following and state ...

algebra 1 help - simplifying square roots 1) find volume of this prism? v=bwh b...

math - Consider the following 6 relations on the set of real numbers: A) y=2x&#...

algebra2 - How do i enter my answer? so the question is Simplify: √3:(63x^...

Algebra - Simplify the expressions and solve the equations 1. 2√3 - √...

Quantum physics - 1] Given qubit 1 in the state 35|0>+45|1> and qubit 2 in...

math - The number 27+200−−−√−−−−...

Math - Can you show me the work to get these answers also? A.Solve each equation...

how do i enter my answer - √4:(32x^11y^15)/√4:(2x^3y^-2) for this ...